ETHNOSCIENCE STUDY OF RUMAH GADANG: THE RECONSTRUCTION OF INDIGENOUS SCIENCE INTO SCIENTIFIC KNOWLEDGE - Nurul Annisa; Skunda Diliarosta (SEMESTA: Journal of Science Education and Teaching, 2021)
Rumah Gadang is a traditional Minangkabau house. The design of Rumah Gadang was made by Minangkabau’s ancestors using the Indigenous Sciences of that era. The intend of this study was to reconstruct the Indigenous Sciences of Rumah Gadang into scientific knowledges that has been widely known today. The expected benefit of this study was to classify the scientific knowledges of Rumah Gadang so as to increas the wealth of Indonesia Ethnoscience. The method of this study was qualitatif descriptive. The study was conducted in Istano Baso Pagaruyuang Batusangkar, West Sumatra. The data were collected through direct observations and document study about Rumah Gadang, in-dept interviews, and also scientific literature about Rumah Gadang. The data were analyzed using the ethnoscience approach. The conclusion was that there were the content of scientific knowledges in the Rumah Gadang which were categorized into 4 fields of science, they were: The Pythagorean Theorem, Substance Pressure, Seismology, and Substance Properties.